2016
DOI: 10.2147/copd.s109700
|View full text |Cite
|
Sign up to set email alerts
|

What else should we know about experiencing COPD? A narrative review in search of patients’ psychological burden alleviation

Abstract: The present paper is a narrative review focusing on the psychological impact, identification of protective factors, and interventions minimizing the psychological burdens of chronic obstructive pulmonary disease (COPD). The research reviews studies on neurocognitive functions, personality, emotional problems, and health-related quality of life. This is done with regard to resources as well as activities enabling or enhancing a patient’s adaptation. PubMed and PsychArticles databases were searched for relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…Signs of neurological and psychological burden of people suffering from chronic respiratory diseases as COPD emerged from literature. 38 In particular, using validated questionnaires, several studies revealed COPD patients’ elevated scores on hypochondria, depression, introversion, anxiety, sensitiveness, despair, and hostility due to their living with this condition. 39 , 40 However, narrative research is shown to be more informative than data from questionnaires, being able to delve into the causes of this psychological burden.…”
Section: Discussionmentioning
confidence: 99%
“…Signs of neurological and psychological burden of people suffering from chronic respiratory diseases as COPD emerged from literature. 38 In particular, using validated questionnaires, several studies revealed COPD patients’ elevated scores on hypochondria, depression, introversion, anxiety, sensitiveness, despair, and hostility due to their living with this condition. 39 , 40 However, narrative research is shown to be more informative than data from questionnaires, being able to delve into the causes of this psychological burden.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is characterized by progressive and nonreversible narrowing or inflammation of the airways or alveoli in the lungs [ 3 , 4 ]. People with COPD experience symptoms such as breathlessness, frequent chest infections, reduced ability to exercise, and impaired day-to-day functioning [ 5 - 7 ]. COPD and its treatment cost the UK’s National Health Service (NHS) approximately 800 million pounds annually [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is usually progressive and associated with a chronic inflammatory response in the airways due to noxious particles or gases (1). COPD is increasingly recognized as systemic and heterogeneous, and may involve skeletal muscle dysfunction (2,3), heart diseases (4), nutritional dysfunctions (5), biochemical changes (6), osteoporosis (7), psychological disorders (8), as well as the impairment of pulmonary mechanics (9).…”
Section: Introductionmentioning
confidence: 99%